RAPID IMPROVEMENT STRATEGIES BASED ON BUDDHADHAMA OF CHID EVELOPMENT CENTERS UNDER THE MUNICIPALITY - Thappasid , Itsayaporn; Ruangsanka , Rawing; Chaisuk, Peravat (Journal of Educational Review Faculty of Education in MCU, 2024)
The objectives of research article are to 1) evaluate strategies for rapid development according to the Buddhist principles of the municipal child development center, 2) offer strategies for rapid development according to Buddhist principles of child development centers under municipalities. It is a mixed method research with qualitative research regulations, the research steps include: 1) Evaluate the strategy for progressive development according to Buddhist principles of child development centers under the municipality. According to the 4-sided inspection standards of Stufflebeam by distributing evaluation forms to Heads of Child Development Center, 361people, 2) Improve, edit and present strategy for rapid development according to Buddhist principles of child development centers under the municipality to the thesis advisor. The study showed that 1) Evaluation of the progressive development strategy according to Buddhist principles of the municipal child development center found that overall, the aspect had the highest average at the highest level was accuracy. The average sorted from highest to lowest were usefulness, appropriateness and feasibility, respectively. 2) Strategy for rapid development according to Buddhist principles of child development centers under the municipality. There were 4 important elements, consisting of vision, which was that the child development center having an excellent standards and quality of learners in leaps and bounds; 3 missions; 3 objectives; 3 goals, ; and 3 strategies. The strategies included 1) strategies for creating a disciplinary organization: consisting of 5 plans; 2) strategies for developing teachers’ ideas and minds to be excellent: consisting of 4 plans; and 3) strategies for developing teachers’ ideas and minds to be excellent, consisting of 2 plans.